ADAB GURU TERHADAP MURID PERSPEKTIF IMAM AL-GHAZALI DI DALAM KITAB BIDĀYAH AL-HIDĀYAH - Ramli, Muhamad; Sayuti, Ahmad (ADDABANA: Jurnal Pendidikan Agama Islam, 2022)
Abstract: This study aims to determine the concept of teacher etiquette towards students from the perspective of Imam al-Ghazali in the Bidāyah al-Hidāyah book and its relevance to the current educational context. This type of research is library research, with data collection through documentation techniques. This research was conducted with a qualitative descriptive approach and using content analysis techniques. Based on the results of the study, the concept of a teacher's adab towards students from Imam al-Ghazali's perspective there are fourteen, namely: Iḥtimāl (ready to bear the burden), al-Ḥilm (being polite), being seated with authority, avoiding arrogance, being Tawāḍu' ( humble), not fond of playing games and joking, gentle to students, guiding students with low IQ to the maximum, not scolding students with low IQ, not ashamed to say "I don't know", focusing on people asking questions, accepting arguments/arguments, preventing students from studying dangerous knowledge, warning students in seeking knowledge that is not pleasing to Allah, preventing students from being busy studying fard kifayah science before completing their obligation to study fard 'ain science. The concept of the adab of a teacher towards students which has been outlined by Imam al-Ghazali in the book Bidāyah al-Hidāyah, in general is still relevant to the current educational context, because the concept is still in line with educational theories that apply at this time. Keywords: Etiquette of Teachers and Students, Imam al-Ghazali, the Book of Bidāyah al-Hidāyah. Abstrak: Penelitian ini bertujuan untuk mengetahui konsep adab guru terhadap murid perspektif  imam al-Ghazali di dalam kitab Bidāyah al-Hidāyah serta relevansinya dengan konteks pendidikan saat ini. Jenis penelitian ini adalah penelitian kepustakaan (Library Research), dengan pengumpulan data melalui teknik dokumentasi. Penelitian ini dilakukan dengan pendekatan deskriftif kualitatif serta menggunakan teknik analisis isi (Content Analysis). Berdasarkan hasil penelitian, konsep adab seorang guru terhadap murid perspektif Imam al-Ghazali ada empat belas, yaitu: Iḥtimāl (siap menanggung beban), al-Ḥilm (bersikap santun), bersikap duduk dengan penuh kewibawaan, menghindari sikap sombong, bersikap Tawāḍu‘ (rendah hati), Tidak gemar bermain-main dan senda gurau, lemah lembut kepada murid, membimbing murid yang rendah IQ-nya dengan maksimal, tidak memarahi murid yang rendah IQ-nya, tidak malu berkata “Aku tidak tahu”,  memusatkan perhatian terhadap orang yang bertanya, menerima hujah/argumen, mencegah murid mempelajari ilmu yang membahayakan, memperingatkan murid dalam menuntut ilmu yang tidak diridhai Allah, mencegah murid sibuk mempelajari ilmu fardu kifayah sebelum selesai kewajibannya mempelajari ilmu fardu ‘ain. Konsep adab seorang guru terhadap murid yang telah digariskan oleh Imam al-Ghazali di dalam kitab Bidāyah al-Hidāyah, secara umum masih relevan dengan konteks pendidikan saat ini, karena konsep tersebut masih sejalan dengan teori-teori pendidikan yang berlaku pada saat ini. Kata kunci: Adab Guru dan Murid, Imam al-Ghazali, Kitab Bidāyah al-Hidāyah.